1996
DOI: 10.1021/bi9511649
|View full text |Cite
|
Sign up to set email alerts
|

Animal and Plant Cell Lysates Share a Conserved Chaperone System That Assembles the Glucocorticoid Receptor into a Functional Heterocomplex with hsp90

Abstract: The hormone-binding domain of the glucocorticoid receptor must be bound to heat shock protein (hsp) 90 for it to have a high-affinity steroid-binding conformation. Cell-free assembly of a glucocorticoid receptor-hsp90 heterocomplex is brought about in reticulocyte lysate by a preformed protein-folding complex containing hsp90, hsp70, and other proteins [Hutchison, K.A., Dittmar, K. D., & Pratt, W.B. (1994) J. Biol. Chem. 269, 27894-27899]. In this "foldosome" system, hsp70 is required for assembly of the recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…By using a TAP-tagged hybrid transcription factor as bait, HSP70 and HSP60 were co-purified. This result was verified by former reports (Dittmar et al, 1997;Stancato et al, 1996). Through the TAP strategy, Liu et al demonstrated that Hsp90 associated with the plant resistance protein N , which meant that Hsp90 plays an important role in plant defense (Kanzaki et al, 2003;Takahashi et al, 2003).…”
Section: Tap In Plantssupporting
confidence: 76%
“…By using a TAP-tagged hybrid transcription factor as bait, HSP70 and HSP60 were co-purified. This result was verified by former reports (Dittmar et al, 1997;Stancato et al, 1996). Through the TAP strategy, Liu et al demonstrated that Hsp90 associated with the plant resistance protein N , which meant that Hsp90 plays an important role in plant defense (Kanzaki et al, 2003;Takahashi et al, 2003).…”
Section: Tap In Plantssupporting
confidence: 76%
“…In some cellular processes, such as activation of steroid hormone receptors, Hsp70 is known to act in a large chaperone complex involving Hsp90 and a variety of co-chaperones including Hop (Hsp70-Hsp90 organizing protein) (Frydman and Hö hfeld, 1997; Pratt and Toft, 1997). Hsp90 and Hop are found in plants (Hernandez Torres et al, 1995;Boston et al, 1996), and the same complex of chaperones exists in plants, as evidenced by the substitution of wheat germ lysate for reticulocyte lysate in steroid receptor activation reactions (Stancato et al, 1996). However, addition of human Hsp90 had no effect on the yield or rate of refolding, and supplementation of the system with Hop plus Hsp90 only moderately increased the apparent rate constant of refolding (Table I).…”
Section: Eukaryotic or Prokaryotic Hsp70 And Co-chaperones Support Himentioning
confidence: 91%
“…The second pathway involves an intracellular steroid-activated receptor complex to directly regulate the transcription of genes by binding to the promoter [45]. In plants, although a chaperon heterocomplex similar to that of intracellular steroid receptor in animal has been identified [46][47][48], neither the candidate gene encoding a putative intracellular receptor of BR has been found in the Arabidopsis genome [49], nor evidence suggested the existence of BR intracellular receptor. However, three BRI1 homologue were identified in Arabidopsis genome [49].…”
Section: Br May Regulate Rav1 Through a Bri1-independent Signal Pathwaymentioning
confidence: 99%